Cutting-edge space tourism - Kurtz, Kevin (Searchlight books. New frontiers of space., 2020)
Defines space tourism and informs of the main companies who are investing in its development. Examines the types of vehicles being developed to take people to space and discusses the training that may be involved for tourist safety. Projects the future of space tourism travel and notes the timeframes companies expect to complete their innovations. Incorporates boxed captions to accompany photographs, instructions for a 3D printer activity, resources for further topic research, and a glossary.